Individual Brain Charting dataset extension, third release for movie watching and retinotopy data - Ana Luísa Pinho; Hugo Richard; Ana Fernanda Ponce; Michael Eickenberg; Alexis Amadon; Elvis Dohmatob; Isabelle Denghien; Juan Jesús Torre; Swetha Shankar; Himanshu Aggarwal; Alexis Thual; Thomas Chapalain; et al. (Scientific Data, 2024)
Abstract The Individual Brain Charting (IBC) is a multi-task functional Magnetic Resonance Imaging dataset acquired at high spatial-resolution and dedicated to the cognitive mapping of the human brain. It consists in the deep phenotyping of twelve individuals, covering a broad range of psychological domains suitable for functional-atlasing applications. Here, we present the inclusion of task data from both naturalistic stimuli and trial-based designs, to uncover structures of brain activation. We rely on the Fast Shared Response Model (FastSRM) to provide a data-driven solution for modelling naturalistic stimuli, typically containing many features. We show that data from left-out runs can be reconstructed using FastSRM, enabling the extraction of networks from the visual, auditory and language systems. We also present the topographic organization of the visual system through retinotopy. In total, six new tasks were added to IBC, wherein four trial-based retinotopic tasks contributed with a mapping of the visual field to the cortex. IBC is open access: source plus derivatives imaging data and meta-data are available in public repositories.